Sexual dimorphism in ratio of second and fourth phalanges and metacarpals: A retrospective study - M, Vijaywargiya; Jain, Megha; Shidhaye, P (International Journal of Medical Research and Review, 2016)
Introduction: There are many features in humans which exhibit sexual dimorphism. A unique feature showing this gender differentiation is the ratio of lengths of index and ring fingers. Sexual dimorphism in finger lengths has been studied across the globe, wherein ethnic and racial variations in digit ratio have been reported. Our studywas conducted in the central Indian population, where no such study was done till now. Aim: To study the prevalence of sexual dimorphism in central Indian population using ratio of phalangeal and metacarpal length of index and ring fingers. Methodology: This is a retrospective radiological study done on left hand of 42 males and 49 females of age 20 years and above. The lengths of phalanges and metacarpals of index and ring fingers were measured on X rays films and their ratios were taken and analyzed statistically. Result: There were no statistically significant variations observed in the ratios of the index and ring fingers between the two sexes in the data taken from central Indian population.